2012
DOI: 10.1371/journal.pone.0034322
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DNA Polymerase Zeta Reduces the Mitochondrial Mutability Caused by Pathological Mutations in DNA Polymerase Gamma in Yeast

Abstract: In yeast, DNA polymerase zeta (Rev3 and Rev7) and Rev1, involved in the error-prone translesion synthesis during replication of nuclear DNA, localize also in mitochondria. We show that overexpression of Rev3 reduced the mtDNA extended mutability caused by a subclass of pathological mutations in Mip1, the yeast mitochondrial DNA polymerase orthologous to human Pol gamma. This beneficial effect was synergistic with the effect achieved by increasing the dNTPs pools. Since overexpression of Rev3 is detrimental for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…In agreement with in vitro data, genetic studies have demonstrated that yeast pol ζ is not only necessary for damage-induced nuclear and mitochondrial genome mutagenesis, it also promotes accurate bypass of some DNA lesions (Baruffini et al , 2012; Baynton et al , 1999; Bresson and Fuchs, 2002; Kalifa and Sia, 2007; Zhang et al , 2006). On all damaged templates tested, pol ζ was a great deal less efficient at incorporating a nucleotide opposite the damaged bases than extending the resulting primer terminus, consistent with the idea that its primary role in lesion bypass is confined to the elongation step, while the incorporation step depends on other polymerases.…”
Section: Biochemical Properties Of Tls Polymerasessupporting
confidence: 73%
“…In agreement with in vitro data, genetic studies have demonstrated that yeast pol ζ is not only necessary for damage-induced nuclear and mitochondrial genome mutagenesis, it also promotes accurate bypass of some DNA lesions (Baruffini et al , 2012; Baynton et al , 1999; Bresson and Fuchs, 2002; Kalifa and Sia, 2007; Zhang et al , 2006). On all damaged templates tested, pol ζ was a great deal less efficient at incorporating a nucleotide opposite the damaged bases than extending the resulting primer terminus, consistent with the idea that its primary role in lesion bypass is confined to the elongation step, while the incorporation step depends on other polymerases.…”
Section: Biochemical Properties Of Tls Polymerasessupporting
confidence: 73%
“…The same levels of rescue can be achieved by deletion of SML1 , which encodes a protein that inhibits the ribonucleotide reductase activity by binding and sequestering Rnr1 (Chabes et al, 1999 ; Zhao et al, 2000 ). The deletion of SML1 had the same effect of RNR1 overexpression both on the mip1-1 mutant and on the pathological Mip1 variants (Zhao et al, 1998 ; Baruffini et al, 2006 , 2012 ).…”
Section: Mip1 Interactionsmentioning
confidence: 95%
“…POLG is also able to bypass 8-oxoG and exocyclic DNA adducts that gives rise to increased mutagenicity [112, 113]. Both Polζ and Rev1 have been identified to have a role in yeast mitochondrial genome maintenance where overexpression of these enzymes led to a reduction in point mutations in the mtDNA [114, 115]. More recently, Polζ was detected in the mitochondria of mammalian cells and elevated expression of the enzyme in breast tumors was associated with cell migration and invasion [116].…”
Section: Mitochondrial Dna Genome Maintenancementioning
confidence: 99%